Energy policy constraints and perspectives in Russia - Werner Gumpel (Intereconomics, 1996)
Once one of the world's most important energy producers, Russia is increasingly incapable of maintaining energy supplies to its industries and private households. However, the crisis in the energy sector has also become an ecological crisis. What chances are there for finding a solution to this double crisis?
Keywords: 330